2014
DOI: 10.2217/pgs.14.46
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Genetic or Epigenetic Variation in Insulin Growth Factors and Antipsychotic-Induced Metabolic Disturbances in a Cross-Sectional Sample

Abstract: There was a significant association between IGF2 methylation and genotype, but no significant association between genetic or epigenetic variability and metabolic parameters in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Further work is needed in this area to begin to truly analyze pharmacoepigenetic-directed DNA methylation changes in bipolar disorder. Within schizophrenia, the main utilizers of SGAs, candidate epigene analyses have yielded mixed results when correlating methylation differences to metabolic outcomes [19,3840] . We previously identified global hypomethylation in female schizophrenia subjects using the linear interspersed nuclear elements 1 (LINE1) assay [39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is needed in this area to begin to truly analyze pharmacoepigenetic-directed DNA methylation changes in bipolar disorder. Within schizophrenia, the main utilizers of SGAs, candidate epigene analyses have yielded mixed results when correlating methylation differences to metabolic outcomes [19,3840] . We previously identified global hypomethylation in female schizophrenia subjects using the linear interspersed nuclear elements 1 (LINE1) assay [39] .…”
Section: Discussionmentioning
confidence: 99%
“…In the only other study to investigating gene-specific methylation in SGA-induced metabolic side effects in severe mental illness [40] , Moons and colleagues, found no associations between DNA methylation of IGF genes 1 or 2 and metabolic side effects. However, they did identify associations between variants within the IGF genes and IGF methylation which may suggest a link between DNA variation and DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was supported by identified associations between a global measure of DNA methylation and AAP‐induced insulin resistance within bipolar disorder . In the only candidate gene study to date, Moons and colleagues found no associations between AAP‐induced metabolic side effects and genetic or epigenetic variability in the insulin‐like growth factor 2 ( IGF2 ) gene …”
mentioning
confidence: 98%
“…Our systematic review yielded 29 studies (Table 1). Eighteen studies analyzed methylation in patients with schizophrenia, four studies in patients with bipolar disorder, and seven studies in a combined sample of patients with schizophrenia and bipolar disorder. The majority (n=22) of studies included observational sampling, such as cross‐sectional or case‐control studies, and the remaining analyzed changes in a prospective manner.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly employed measurement utilized restriction enzymes (five studies) followed by transposable elements (two studies) and ELISA (one study). 26 Obs 133 SCZ AAP and TAP Blood Global Cheng et al 27 Obs and prosp 30 Obs 172 BD olanzapine and quetiapine Blood d EWAS and genespecific Kinoshita et al 31 Prosp 21 SCZ olanzapine Blood EWAS Li et al 32 Obs 92 SCZ; 99 BD; 92 HC AAP and TAP Blood global Lott et al 33 Obs 85 SCZ NR blood gene-specific Melas et al 34 Obs 177 SCZ; 171 HC AAP and TAP Blood Global and genespecific Mill et al 35 Obs 35 SZ; 35 BD; 35 HC NR Brain EWAS Miura et al 36 Prosp 34 SCZ risperidone Blood Gene-specific Moons et al 37 Obs 438 SCZ AAP and TAP Blood Gene-specific Nour El Huda et al 38 Obs 138 SCZ; 132 HC AAP and TAP Blood Gene-specific Rukova et al 39 Prosp 20 SCZ; 220 HC NR Blood EWAS Shi et al 40 Prosp 288 SCZ risperidone Blood Gene-specific Swathy et al 41 Obs 184 SCZ; 330 HC NR Blood Global Tang et al 42 Prosp 82 SCZ AAP and TAP Blood Gene-specific Venugopal et al 43 Prosp 47 SCZ; 47 HC AAP Blood Gene-specific Zong et al 44 Obs 279 SCZ; 265 HC AAP and TAP Blood Gene-specific Details of 29 studies included in the systematic review including study design, type of antipsychotic within study, sample type for DNA methylation analysis, and overall DNA methylation strategy. AAP = atypical antipsychotic; BD = bipolar disorder; HC = healthy control; MDD = major depressive disorder; NR = not reported; obs = observational; PR = primary relative; pros = prospective; scz = schizophrenia; TAP = typical antipsychotic; UPR = unaffected primary relative.…”
Section: Global Methylation Studiesmentioning
confidence: 99%